Effects of hemodynamic shear stress on circulating breast cancer cells - Khairunisa Liyana Abdul Malek (2015)
The ability of a cancer cell to relocate to a distal location and subsequently form tumours largely depends on its ability to withstand hemodynamic shear stress in the blood vessel. While previous studies have shown that cancer cells have an enhanced resistance towards these intense conditions, little is known whether a tumour cell's metastatic ability is correlated to its ability to survive high shear stress levels over a prolonged period of time. In this project, three lines of metastatic breast cancer cells, 231-C3, 231-M1 and 231-M1A were circulated in a microfluidic model mimicking the blood circulatory system over four different time periods: 2 hours, 4 hours, 9 hours and 18 hours while being exposed to three different hemodynamic shear stress at values of 15 dyn/cm2, 30 dyn/cm2 and 45 dyn/cm2. Results were obtained experimentally using MTT and also imaging techniques. Subsequently, these cells were evaluated for their post circulation cell viabilities and apoptosis rates. Additionally, post circulation growth rates were also studied. This study will show that the metastatic ability of the cancer cell is related to the resistance against shear stress while showing that the shear stress intensity and the time cells remain in circulation are two key factors that affects cell viability and cell apoptosis rates.